Lost female talent: Gender differences in college aspirations and expectations in Germany - Melinda Erdmann; Marcel Helbig; Marita Jacob (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
Our study focuses on the gender gap in college aspirations and enrolment among high school students in Germany. We build on socialisation theory, rational choice theory, and formal restrictions to college access to explain gender differences in idealistic college aspirations, realistic college expectations, and the disparities between the two. Specifically, we examine the prevalence of 'pessimistic' college expectations, where college aspirations are higher than expectations, which we expect to be more likely among young women than young men. By analysing survey data from 1,766 upper secondary students in Germany, we find that women are equally interested in pursuing higher education as their male counterparts. They even express higher aspirations for college enrolment. However, women are more pessimistic than men about realising their aspirations. While factors such as the subjective probability of success and perceived costs impact both genders, young women are also affected by formal restrictions limiting entry to their preferred fields of study.
Keywords: 300